2022
DOI: 10.3390/cells11071215
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of DNA Damage Response in Patient-Derived Glioblastoma Cells before and after Radiation and Temozolomide Treatment

Abstract: Glioblastoma is a highly aggressive, invasive and treatment-resistant tumour. The DNA damage response (DDR) provides tumour cells with enhanced ability to activate cell cycle arrest and repair treatment-induced DNA damage. We studied the expression of DDR, its relationship with standard treatment response and patient survival, and its activation after treatment. The transcriptomic profile of DDR pathways was characterised within a cohort of isocitrate dehydrogenase (IDH) wild-type glioblastoma from The Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…This lack of synergistic interaction observed in TMZ+RT treated cell lines is worth noting and has been observed in U251 and U373MG cell lines [ 41 , 42 ]. Our previous work showed that glioblastoma cells treated with TMZ or RT elicits different patterns of DDR upregulation, and when combined, a lower response of DDR genes is observed [ 43 ]. Thus, the addition of DNA-damaging agents (i.e., TMZ and RT) that induce slightly different but overlapping activation of DDR pathways at different time points may hinder synergistic responses, as the activation of DDR from one agent may prime the cell for repair of the damage induced by the other.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of synergistic interaction observed in TMZ+RT treated cell lines is worth noting and has been observed in U251 and U373MG cell lines [ 41 , 42 ]. Our previous work showed that glioblastoma cells treated with TMZ or RT elicits different patterns of DDR upregulation, and when combined, a lower response of DDR genes is observed [ 43 ]. Thus, the addition of DNA-damaging agents (i.e., TMZ and RT) that induce slightly different but overlapping activation of DDR pathways at different time points may hinder synergistic responses, as the activation of DDR from one agent may prime the cell for repair of the damage induced by the other.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of synergistic interaction observed in TMZ+RT treated cell lines is worth noting, and has been observed in U251 and U373MG cell lines 43,44 . Our previous work showed that glioblastoma cells treated with TMZ or RT elicits different patterns of DDR upregulation, and when combined, a lower response of DDR genes is observed 21 . Thus, the addition of DNA-damaging agents (i.e., TMZ and RT) that induce slightly different but overlapping activation of DDR pathways at different time points may hinder synergistic responses, as the activation of DDR from one agent may prime the cell for repair of the damage induced by the other.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-day time point was chosen as untreated cells reached a high level of confluence after cell seeding by day 7. Cell viability was assessed using the MTT cell viability assay as previously described 21 . The IC50 of gartisertib and berzosertib in each respective cell line was determined using the MTT cell viability assay.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…7) RPA3 is part of the three-subunit replication protein A (RPA) complex involved in homologous recombination and double strand break repair, and has been implicated in glioblastoma survival outcomes. 40 FoxM1 has been reported to promote stemness, radioresistance and mesenchymal transition in GBM. Radioresistance in GBM is known to be conferred by glioblastoma stem-like cells and is a key factor of GBM treatment resistance.…”
Section: Effect Of Rpa3 and Blvra Silencing In Npcsmentioning
confidence: 99%